“Two Minds Don’t Blink Alike”: The Attentional Blink Does Not Occur in a Joint Context - Constable, Merryn D.; Pratt, Jay; Welsh, Timothy N. (Frontiers in Psychology, 2018)
Typically, when two individuals perform a task together, each partner monitors the other partners’ responses and goals to ensure that the task is completed efficiently. This monitoring is thought to involve a co-representation of the joint goals and task, as well as a simulation of the partners’ performance. Evidence for such ‘co-representation’ of goals and task, and ‘simulation’ of responses has come from numerous visual attention studies in which two participants complete different components of the same task. In the present research, an adaptation of the attentional blink task was used to determine if co-representation could exert an influence over the associated attentional mechanisms. Participants completed a rapid serial visual presentation task in which they first identified a target letter (T1) and then detected the presence of the letter X (T2) presented 1-7 letters after T1. In the individual condition, the participant identified T1 and then detected T2. In the joint condition, one participant identified T1 and the other participant detected T2. Across two experiments, an attentional blink (decreased accuracy in detecting T2 when presented 3 letters after T1) was observed in the individual condition, but not in joint conditions. A joint attentional blink may not emerge because the co-representation mechanisms that enable joint action exert a stronger influence at information processing stages that do not overlap with those that lead to the attentional blink.